International African Bibliography - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
International African Bibliography published quarterly ISSN 0020-5877, subscription rate for Volume 18, 1988 UKL 44 or USD 80 elsewhere. Single copies and back numbers UKL 13 or USD 23 (private subscriptions are half price)